2017
DOI: 10.1007/s40858-017-0140-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing sequence diversity of Groundnut rosette disease agents and the distribution of Groundnut rosette assistor virus in major groundnut-producing regions of Ghana

Abstract: The incidence of Groundnut rosette assistor virus (GRAV) in farmers' fields and sequence diversity of groundnut rosette disease (GRD) agents were assessed in the three northern groundnut production regions of Ghana. GRAV incidence was high (69.5 to 75.0%) but not significantly different between the regions. Nucleotide sequencing of GRAV coat protein (CP) gene revealed 99-100% identity among the Ghanaian isolates and 97-100% similarity to GRAV sequences from Nigeria and Malawi for both nucleotide and predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Kenyan GRAV CP isolates exhibited closest identities with Malawian isolates than Nigerian and Ghanaian isolates. This findings concurs with [14] and [23], who observed closer identity between sequences from the same geographical region as compared to those from separate geographical regions. In the study, [14] found that Kenyan isolates of GRAV CP gene shared 98% nucleotide identity with Malawian isolates as compared to 96-97% with those from Nigeria.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Kenyan GRAV CP isolates exhibited closest identities with Malawian isolates than Nigerian and Ghanaian isolates. This findings concurs with [14] and [23], who observed closer identity between sequences from the same geographical region as compared to those from separate geographical regions. In the study, [14] found that Kenyan isolates of GRAV CP gene shared 98% nucleotide identity with Malawian isolates as compared to 96-97% with those from Nigeria.…”
Section: Discussionsupporting
confidence: 91%
“…In the study, [14] found that Kenyan isolates of GRAV CP gene shared 98% nucleotide identity with Malawian isolates as compared to 96-97% with those from Nigeria. [23], observed that Ghanaian GRAV CP gene sequence isolates had 98-99% nucleotide identity as compared to 97-99% with Malawian isolates. Such differences due to geographical distances could be as a result of differences in environmental conditions that bring about variations in evolution of the viruses.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The lack of information on the distribution of the disease and viral isolate variation hampers the management, and development of control measures aimed at reducing losses [30]. Since GRD epidemics occur without warning, an in depth study of the variability in the three components of groundnut rosette should be thoroughly investigated.…”
Section: Biotechnological Approaches In Management Of Grdmentioning
confidence: 99%